The effect on paraoxonase and arylesterase activities of bee pollen against deltamethrin in Cyprinus carpio - Eroglu, Mucahit; Yonar, M. Enis; Yonar, Serpil Mise; Ispir, Unal; Ural, M. Sener; Silici, Sibel (Taylor & Francis Ltd, 2026)
This study aimed to determine whether dietary bee pollen protects common carp (Cyprinus carpio) from deltamethrin (DM)-induced oxidative stress by modulating serum paraoxonase (PON) and arylesterase (ARE) activities. DM, a widely used pyrethroid insecticide, can impair antioxidant defenses in aquatic organisms. PON and ARE, two HDL-associated enzymes with antioxidant properties, were used as biomarkers to evaluate oxidative stress. Fish were exposed to two sublethal concentrations of DM (0.018 and 0.036 mu g/L) for 14 days, with or without dietary supplementation of 2% chestnut-origin bee pollen. Results showed that while DM exposure significantly reduced serum PON and ARE activities, indicating oxidative stress and enzyme inhibition, bee pollen supplementation effectively counteracted these effects in a dose-dependent manner (p < 0.05). However, co-administration of the bee pollen partially restored both enzyme activities in a dose-dependent manner (p < 0.05). The improvement suggests that bee pollen, rich in flavonoids, phenolic compounds, and vitamins, exerts antioxidant effects that mitigate DM-induced toxicity. Bee pollen alone did not significantly alter PON or ARE activity compared to controls, confirming its safety and potential as a dietary supplement. Overall, this study provides evidence that bee pollen can serve as a natural antioxidant supplement to protect aquatic organisms against pesticide-induced oxidative damage, thereby contributing to the sustainable health management of aquaculture. These findings demonstrate that bee pollen can protect against pesticide-induced oxidative damage and may serve as a natural therapeutic agent in aquaculture.
Keywords: Bee pollen; deltamethrin; oxidative stress; paraoxonase; arylesterase; Cyprinus carpio